2009
DOI: 10.1002/elan.200804495
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Behavior and Amperometric Detection of Morphine on ITO Electrode Modified with Directly Electrodeposited Gold Nanoparticles

Abstract: A gold nanoparticles (AuNPs) modified indium tin oxide (ITO) film coated glass electrode was prepared via a novel electrochemical deposition technique. The UV-visible spectrum and SEM indicated that the AuNPs on ITO electrode surface were spherical shape and quite symmetric distributed. The modified electrode exhibited excellent catalytic activity for the oxidation of morphine (MO). At optimal experimental condition, the oxidation current was responsive with the MO concentrations ranging from 8.0 Â 10 À7 to 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…If the low potential is above −0.4 V, the gold becomes hard to be nucleated. At potential more negative than −0.4 V, a nucleation with a sufficient large overpotential can be achieved to effectively seed the surface with nuclei [30]. So, in the following cycle, AuNPs can start to grow on the surface of electrode.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the low potential is above −0.4 V, the gold becomes hard to be nucleated. At potential more negative than −0.4 V, a nucleation with a sufficient large overpotential can be achieved to effectively seed the surface with nuclei [30]. So, in the following cycle, AuNPs can start to grow on the surface of electrode.…”
Section: Resultsmentioning
confidence: 99%
“…The fabrication of AuNPs layer on GC electrode (3 mm dia., CH Instrument) was carried using electrochemical deposition [29,30,31]. GC electrode was polished with aluminum oxide powder and electrochemically polished in 1 M H 2 SO 4 solution to remove any organic binders and contamination that occurs at electrode surface.…”
Section: Methodsmentioning
confidence: 99%
“…This also demonstrates the fact that the results obtained at the sensor are reproducible in analytical applications. In Table 1, some of the analytical characteristics of the developed method were compared with those previously reported by others [20][21][22][23][24][25][26][27][28][29][30]. As it can be seen, the capabilities of the proposed sensor are superior in most cases than the others.…”
Section: Dpv Technique For Quantification Of Morphine and Acetaminophenmentioning
confidence: 80%
“…Electrochemical analysis, which is safe, rapid, simple, and low-cost, has become of growing importance in medicine and biotechnology, environmental monitoring, and different applications in industrial process control. In the last decade, a few reports can be found to have used electrochemical methods for morphine determination [20][21][22][23][24][25][26][27][28][29][30]. There is also an access to a review manuscript that reported analytical methodologies for the determination of morphine and its metabolites [31].…”
Section: Introductionmentioning
confidence: 96%
“…13 Using the same electrodes, the same group reported on the electrocatalytic oxidation of glucose, 14 a horseradish peroxidase-based hydrogen peroxide sensor, 15 and the amperometric detection of morphine. 16 As an example of a different substrate and Au precursor, Rassaei et al reported on the electroaggregation of commercially available 5-nm AuNPs on a boron-doped diamond electrode surface. 17 The electroaggregation process formed a highly reactive mesoporous Au film, which was applied to an electrochemical analysis of As(III).…”
Section: Electrochemical Deposition Of Metal Npsmentioning
confidence: 99%